Ius publicum in iure privato - Žepič, Vid (Zgodovinski časopis, 2023)
The aim of this article is to provide an analysis of the public law elements embedded within the fabric of Roman private law. The article focuses on legal relationships regulating private law subjects which were characterised by a particularly large degree of involvement by legal entities governed by public law. Public legal entities performed a threefold role in these seemingly private law relationships: they exercised authority, acted as supervisors, and served as business partners. By virtue of its attempts to accommodate the participation of legal entities subject to public law, Roman law created a distinct category of public-private legal relationships. The central goal of this article is to describe the form and extent to which these relationships deviated from the foundational tenets of the Roman private law.
Keywords: birokratizacija; bureaucratization; delitev prava; division of law; history of administrative law; legal entities governed by public law; pravne osebe javnega prava; rimsko javno pravo; Roman public law; zgodovina upravnega prava